A Critique of Steven Vogel's Social Constructionist Attempt to Overcome the Human/Nature Dichotomy. (October 2021) - Lie, Svein Anders Noer
This paper analyses Steven Vogel's claim that his account of a post-natural environmental philosophy solves the dualism problem within the field. Through what I will call a novel critique of social constructionism, this paper examines whether Vogel's attempt succeeds or whether it reinforces the problem he wants to solve. Could the ontological foundations of social constructivism themselves be in conflict with Vogel's stated aim of overcoming the human/ nature dualism? The last part of the paper focuses on the significance and role of a post-natural environmental philosophy for the field of environmental philosophy in general.